Bioactive hydroanthraquinones from endophytic fungus Nigrospora sp. BCC 47789. (April 2018) - Kornsakulkarn, Jittra; Choowong, Wilunda; Rachtawee, Pranee; Boonyuen, Nattawut; Kongthong, Surisa; Isaka, Masahiko; Thongpanchang, Chawanee
Graphical abstract: Highlights: The constituents of endophytic fungus Nigrospora sp. BCC 47789 were investigated. A new nigrosporone A and a new naturally occurring nigrosporone B were isolated. The absolute configurations of nigrosporones A and B were also established. Nigrosporone B exhibited broad range of biological activities. Nigrosporone A and fusaquinon A showed only cytotoxic activity. Abstract: A new hydroanthraquinone, nigrosporone A (1), and a new naturally occurring nigrosporone B (2 ), together with eleven known compounds, were isolated from an endophytic fungus, Nigrospora sp. BCC 47789. The structure of nigrosporone A was confirmed by X-ray crystallographic analysis. The absolute configurations of nigrosporone B were determined by the modified Mosher's method. Nigrosporone B exhibited a broad range of biological activities including antimalarial, antitubercular, antibacterial and cytotoxic activities, while nigrosporone A and Fusaquinon A showed only cytotoxic activity.